Apoptosis-inducing factor (AIF) at the crossroad of cell survival and cell death: implications for cancer and mitochondrial diseases - Tran Ngoc Anh Nguyen; Hong-Toan Lai; Romain Fernandes; Filippo G Dall’Olio; Camille Blériot; Tap Ha-Duong; Catherine Brenner (Cell Communication and Signaling)
Abstract Apoptosis-inducing factor (AIF), a mitochondrial NAD(P)H-dependent oxidoreductase, was initially studied as a cell death inducer in a process later named parthanatos. However, it has been revealed that AIF also participates in mitochondrial bioenergetics through interaction with its partner coiled-coil-helix-coiled-coil-helix domain containing 4 (CHCHD4) and involvement in mitochondrial protein import. These dual roles place AIF between pro-survival and pro-death cell fate decisions. In this review, we first describe the structure and the dual functions of AIF, highlighting its structure-function relationships. We then report previously identified AIFM1 mutations and their clinical phenotypes. Finally, we discuss the relevance of AIF in cancer and the potential of targeting this protein for the treatment of cancer.